Motivation and creativity among students: a meta-analysis - Qin, Dan; Che Hassan, Norlizah; Ahmad, Nor Aniza; Yasin, Maizura; Song, Pu (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Motivation has always been regarded as the key role in students’ creativity, this study based on the Amabile’s componential theory of creativity, the motivation, especially intrinsic motivation is positively influence on creativity. "People are most creative when they feel motivated primarily by the interest, enjoyment, satisfaction, and challenge of the work itself, while not by extrinsic motivators.” (Amabile, 2012). Nevertheless, there are many empirical studies that have yielded different results. This meta-analysis study aims to explore the relationship between the two dimensions of motivation (intrinsic and extrinsic) and creativity among students. To exploring the factors that lead to these different outcomes, provide a strong basis for the cultivation and development of students’ creativity. A total of 79 independent effect sizes (n = 18966) were obtained from 28 studies through literatures search. The heterogeneity test showed that the random effect model was suitable. At the result, intrinsic motivation was positively (middle effect size) correlated with creativity while negatively (weak effect size) correlated with extrinsic motivation for students’ creative ability. The sub-group test showed that the relationship between intrinsic/extrinsic motivation and creativity among students was adjusted and influenced by motivational measurements (intrinsic motivation and extrinsic motivation), domains of creativity (general and specific. In general, intrinsic motivation is hard to control by outside, however, the extrinsic motivation could change. Scholars should pay more attention to the effect of intrinsic motivation, extrinsic motivation and its motivational synergy on creativity.